The genomic and molecular landscape of splenic marginal zone lymphoma, biological and clinical implications - Amatta Mirandari; Helen Parker; Margaret Ashton-Key; Benjamin Stevens; Renata Walewska; Kostas Stamatopoulos; Dean Bryant; David G. Oscier; Jane Gibson; Jonathan C. Strefford (Open Exploration Publishing Inc., 2024)
Splenic marginal zone lymphoma (SMZL) is a rare, predominantly indolent B-cell lymphoma constituting fewer than 2% of lymphoid neoplasms. However, around 30% of patients have a shorter survival despite currently available treatments and the prognosis is especially poor for the 5-15% of cases that transform to a large cell lymphoma. Mounting evidence suggests that the molecular pathogenesis of SMZL is critically shaped by microenvironmental triggering and cell-intrinsic aberrations. Immunogenetic investigations have revealed biases in the immunoglobulin gene repertoire, indicating a role of antigen selection. Furthermore, cytogenetic studies have identified recurrent chromosomal abnormalities such as deletion of the long arm of chromosome 7, though specific disease-associated genes remain elusive. Our knowledge of SMZL's mutational landscape, based on a limited number of cases, has identified recurring mutations in KLF2, NOTCH2, and TP53, as well as genes clustering within vital B-cell differentiation pathways. These mutations can be clustered within patient subgroups with different patterns of chromosomal lesions, immunogenetic features, transcriptional signatures, immune microenvironments, and clinical outcomes. Regarding SMZL epigenetics, initial DNA methylation profiling has unveiled epigenetically distinct patient subgroups, including one characterized by elevated expression of Polycomb repressor complex 2 (PRC2) components. Furthermore, it has also demonstrated that patients with evidence of high historical cell division, inferred from methylation data, exhibit inferior treatment-free survival. This review provides an overview of our current understanding of SMZL's molecular basis and its implications for patient outcomes. Additionally, it addresses existing knowledge gaps, proposes future research directions, and discusses how a comprehensive molecular understanding of the disease will lead to improved management and treatment choices for patients.